Anti-Money Laundering and Financial Crime Laws in Malaysia - Zul Kepli, Mohd Yazid; Pillai, Allan Suman (LexisNexis, 2022)
This book explains the legal and regulatory framework for anti-money laundering and financial crime laws in Malaysia.